Miracle Creek - Kim, Angie, 1969- (New York : Sarah Crichton Books/Farrar, Straus and Giroux, 2019)
"A literary courtroom thriller about a mother accused of murdering her eight-year-old autistic son"--
Keywords: Medicine, Experimental -- Fiction; Immigrants -- United States -- Fiction; Koreans -- United States -- Fiction; Legal fiction (Literature)